A Novel Hybrid Nanoparticle Based on Fe 3 O 4 /Tmaoh/Poly(L-Co-D,L Lactic Acid-Co-Trimethylene Carbonate) Prepared Through the Solvent Displacement Method - Pizarro-Arriagada, C; Pizarro-Arriagada, C (Springer International Publishing, 2019)
TMAOH-dispersed nanoparticles of magnetite were first prepared through the reduction–precipitation of ferric chloride with Na 2 SO 3 and NH 4 OH. The TMAOH-dispersed (Fe 3 O 4 ) magnetic nanoparticles were then surface-coated with poly(L-co-D,L lactic acid-co-trimethylene carbonate) (PLDLA-co-TMC) to obtain the corresponding hybrid system (Fe 3 O 4 /TMAOH/PLDLA-co-TMC). Samples of so prepared material were analyzed by Fourier-transform infrared spectroscopy (FTIR), powder X-ray diffraction (XRD), magnetization measurements up to 2.5 T, and Mössbauer spectroscopy. Results indicate that this magnetic iron oxide soon after the synthesis is structurally close enough to a typically pure stoichiometric magnetite. FTIR data support clears evidences confirming the efficiency of the solvent displacement method to assure coating the TMAOH-dispersed (Fe 3 O 4 ) magnetic nanoparticles with the terpolymer while preserves the main chemical structural characteristic of the nanosized magnetite. © 2019, Springer Nature Switzerland AG.